Works of art conservation and research - Swietlik, Justyna Olszewska (Conservation: Science and art series, 2021)
The conservation of a work of art requires efforts that span many areas of specialisation. Before such efforts can commence, however, one needs to explore the historical background of the artefact, determine the technology and technique used in its creation and identify the nature and causes of any damage.